Morphology of temporal region skin in women of different age categories with an additional pathology - Makarchuk O.I. (Морфологія, 2010)
To define structural and functional changes of skin in women of different age groups with an additional internal pathology in this work intraoperative biopsy material of skin of 104 women at the age from 19 to 73 years, that was taken during standard surgery instrumentations for different defects of face skin correction, was investigated. Skin material of temporal region was morphologically processed. To define parameters of microvessels, serial sections was investigated with the help of morphometry. It was determined, that involution dynamic of microvessel condition in papillary layer of derma coincides with grade reduction of relative volume of microvessels bed. There is growth of relative microvessels volume in reticular layer of derma in women of older age groups. Microcirculation age changes include structural disorders of intrapapillary capillary loops, disorganization of arterioles in papillary and reticular layers of derma, disorders of venules because of the changes in microenvironmental fibrillar network. It is typical at the patients with nicotinic dependence, ischemic heart disease, hypertonic disease, a diabetes, and also adiposity of a different degree essential infringement of microvessels bed structure of a skin that gives the basis for allocation of the given contingent of patients as group high intraoperative and postoperative risk at carrying out of operative interventions for correction of face skin involutive changes.